PERSFEKTIF MANAJEMEN DAKWAH TERHADAP BUNUH DIRI - Sihabuddin, M. Amin (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2019)
Abstract : Suicide is an act that is prohibited in Islam. Nevertheless, cases (events) of suicide occur a lot among Muslims. The reason is because: (1) Egoistic suicide (personal business); (2) alturuistic suicide (suicide to fight for others); (3) anomic suicide (suicide because of society in confusion). This condition is exacerbated by the quality of weak faith (dominated by taqlid). To prevent this phenomenon, Islamic preaching is very significant to foster the faith of the Ummah. In this context, it is necessary to have da'wah management to manage, organize, control and evaluate da'wah activities so that Muslims have istiqomah faith characterized by not being afraid in the face of calamities and examinations. Conversely, Muslims who try and make every effort to respond to calamities and tests are created and can take lessons from all challenges by being patient and relying on Allah alone and will give birth to optimistic traits. Keywords: Da'wah Management, Suicide